THE EFFECT OF ENTREPRENEURSHIP CHARACTERISTICS, BUSINESS CAPITAL, AND TECHNOLOGICAL SOPHISTICATION ON MSME PERFORMANCE - Renaldo, Nicholas; Sudarno, Sudarno; Hutahuruk, Marice Br.; Junaedi, Achmad Tavip; Andi, Andi; Suhardjo, Suhardjo (Institut Bisnis dan Teknologi Pelita Indonesia, 2021)
This study aims to analyze the influence of entrepreneurial characteristics, business capital, and technological sophistication on the performance of SMEs. The data collection method used in this study was a questionnaire. The number of respondents as a research sample was 291 MSME owners in Pekanbaru City. The analysis technique used is multiple regression analysis. The findings of this study are that entrepreneurial characteristics have a positive effect on MSME performance, venture capital has a positive effect on MSME performance and technological sophistication has no effect on MSME performance. Advice to MSME owners to consider aspects of technological sophistication in developing their business during the Covid-19 pandemic because using technology, especially in terms of marketing, can reduce direct contact so that human resources owned are protected from the risk of the Corona virus.